OP53 Contrasting cardiovascular mortality trends in Eastern Mediterranean populations – contributions from risk factor changes and treatments: modelling study. (2nd September 2014) - Critchley, J; Capewell, S; O'Flaherty, M; Abu-Rmeileh, N; Sozmen, K; Husseini, A; Fouaud, F; Saidi, O; Romdhane, H; Unal, B; Bandosz, P; Bennett, K; et al.
Abstract : Background: Middle income countries are facing an epidemic of non-communicable diseases, especially coronary heart disease (CHD). We used a previously validated CHD mortality model (IMPACT) to examine recent trends in CHD mortality in Tunisia, Syria, the occupied Palestinian territory (oPt – West Bank) and Turkey. Methods: Data on populations, mortality, patient groups and numbers, treatments and risk factor trends from national and local surveys in each country were collated over two time points. Populations of studied countries and timeframes for this analysis were: Tunisia (10 million, 1997–2009), Syria (19 million, 1996–2006), OPt (2.5 million, 1998–2009) and Turkey (73 million, 1995–2008). We integrated and analysed data using the IMPACT model, with uncertainty explored using probabilistic sensitivity analyses. We reported the percentage of the observed change in CHD deaths explained by changes in uptake of medical and surgical treatments and major CHD risk factors for each country. Results: Risk factor trends: Regional smoking prevalences were high in men, persisting in Syria but decreasing in Tunisia (-11%), oPt (-25%) and Turkey (-45%). Obesity (body mass index) rose by 1–2kg/m 2 and diabetes prevalence increased by 40%–50% in all four countries. Mean systolic blood pressure and cholesterol levels increased in Tunisia and Syria but decreased in oPt and stayed constant in Turkey. Mortality trends: Age adjusted CHD mortality rates rose by 30% in Tunisia (49/10 5 to 64/10 5 ) and by 56% in Syria (108/10 5 to 169/10 5 ). Much of this increase (98% in Tunisia, and 80% in Syria) was attributable to adverse trends in major risk factors, and occurred despite some improvements in treatment uptake. CHD mortality rates fell by 25% in oPt (85/10 5 to 64/10 5 ) and by 17% in Turkey (418/10 5 to 345/10 5 ), with risk factor changes accounting for around 65% and 60% of this reduction respectively. Increased uptake of community treatments accounted for the remainder. The IMPACT model explained approximately 77% of the observed mortality trends in Turkey and oPt, but less in Syria and Tunisia. Results remained fairly consistent following sensitivity analyses. Conclusion: Eastern Mediterranean countries have shown highly heterogeneous trends in blood pressure, blood cholesterol and CHD mortality. Death rates are rising in Tunisia and Syria, whilst Turkey and occupied Palestinian territories demonstrate clear mortality falls, reflecting improvements in major cardiovascular risk factors, plus contributions from community-based medical treatments. However, across the region, smoking prevalence remains very high in men, and obesity and diabetes levels are rising dramatically. Powerful prevention policies exist and should now be implemented.